1993
DOI: 10.1128/aem.59.4.1176-1180.1993
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Mo 6+ -Reducing Bacterium

Abstract: A Mo6+-reducing bacterium (strain 48), which grew on medium supplemented with 200 mM Mo6+, was isolated from stream water obtained from Chengkau, Malaysia. The chemical properties of strain 48 conform to the characteristics of Enterobacter cloacae. Under anaerobic conditions in the glucose-yeast extract medium containing phosphate ion (2.9 mM) and Mo6+ (10 mM), the bacterium reduced Mo6+ to form molybdenum blue. Approximately 27% of Mo6+ added to the medium was reduced after 28 h of cultivation. The reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 24 publications
4
100
0
Order By: Relevance
“…We repeated the experiment using molybdate as the electron-accepting substrate (Ghani et al 1993) instead of laboratory-prepared phosphomolybdate in the enzyme assay, and obtained similar results with no inhibition of molybdate-reducing activity seen (data not shown).…”
Section: Effect Of Respiratory Inhibitorsmentioning
confidence: 70%
See 4 more Smart Citations
“…We repeated the experiment using molybdate as the electron-accepting substrate (Ghani et al 1993) instead of laboratory-prepared phosphomolybdate in the enzyme assay, and obtained similar results with no inhibition of molybdate-reducing activity seen (data not shown).…”
Section: Effect Of Respiratory Inhibitorsmentioning
confidence: 70%
“…cloacae strain 48 and Ser. marcescens strain DRY6 with the optimal ratio of molybdate to phosphate ions found to be between 15 and 25 and between 2AE9 and 5 mmol l )1 , respectively (Ghani et al 1993;Shukor et al 2008b). Campbell et al (1985) reported that at 5 mmol l )1 phosphate, 80 mmol l )1 molybdate was the optimum concentration for supporting molybdate reduction in E. coli K12.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations